Achieving quality construction projects based on harmonious working relationships: clients' and architects' perceptions of contractor performance - Robby Soetanto; David G. Proverbs; Gary D. Holt (2001)
The results of an investigative study aimed at assessing the performance of construction contractors, as perceived by clients and architects in the UK, are presented. The assessment uses predetermined generic performance criteria and involves two measurements, namely perceived importance (I) and perceived performance (P). Importance-performance analyses are then carried out using three measures, namely average satisfaction (D), percentage response (R) and priority rank (PR). Results indicate a need for contractors to improve in most aspects of performance. Generally, architects are found to be less satisfied than clients in regard to overall contractor performance. Furthermore, the perceptions of clients and architects regarding D and PR are broadly similar. It is implied that a well-planned and designed performance improvement strategy on behalf of contractors will address the needs of both clients and architects. Findings will be of interest to contractors embarking on projects with clients and architects. © MCB UP Ltd.